2018
DOI: 10.4274/tjo.89587
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Scheimpflug Tomography Parameters in Subclinical Keratoconus, Clinical Keratoconus and Normal Caucasian Eyes

Abstract: Objectives:To evaluate tomographic and topographic parameters in subclinical and clinical keratoconus eyes by comparing them with normal eyes in a young Caucasian population.Materials and Methods:This cross-sectional study included 88 normal eyes (control group), bilateral data from the preclinical stage of 24 progressive keratoconus eyes (bilateral subclinical keratoconus group), 40 fellow eyes of patients with unilateral keratoconus (fellow eyes group) and 97 eyes with mild keratoconus (clinical keratoconus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 29 publications
2
25
3
Order By: Relevance
“…The present study introduced a powerful formula with 96.8% sensitivity and 94.5% specificity in diagnosis subclinical KC based on morphogeometric, volumetric and clinical parameters (D apexant ‐D apexpost difference, VOL aap ‐1.0 mm, C x , cylinder, CCT and IOP). These sensitivity/specificity values seem to be higher than that of the Sirius KC screening standard algorithm (44.1% sensitivity and 96.3% specificity) and previously reported parameters in detection of subclinical KC (Pinero et al, 2010; Ucakhan et al, 2011; Cui et al, 2016; Hashemi et al, 2016; Huseynli & Abdulaliyeva, 2018; Chan et al, 2018). Furthermore, higher sample size can be considered as another strength of the current study.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The present study introduced a powerful formula with 96.8% sensitivity and 94.5% specificity in diagnosis subclinical KC based on morphogeometric, volumetric and clinical parameters (D apexant ‐D apexpost difference, VOL aap ‐1.0 mm, C x , cylinder, CCT and IOP). These sensitivity/specificity values seem to be higher than that of the Sirius KC screening standard algorithm (44.1% sensitivity and 96.3% specificity) and previously reported parameters in detection of subclinical KC (Pinero et al, 2010; Ucakhan et al, 2011; Cui et al, 2016; Hashemi et al, 2016; Huseynli & Abdulaliyeva, 2018; Chan et al, 2018). Furthermore, higher sample size can be considered as another strength of the current study.…”
Section: Discussioncontrasting
confidence: 52%
“…Table 4 allows comparison of sample size, the best diagnostic parameter(s) and sensitivity/specificity values between the present study and previously published studies, which used similar subclinical KC definition with ours (Pinero et al, 2010; Ucakhan et al, 2011; Cui et al, 2016; Hashemi et al, 2016; Huseynli & Abdulaliyeva, 2018; Chan et al, 2018). Studies that included clinically and topographically normal (also no atypical or suspicious findings) fellow eye of a patient with manifest KC in the other eye (what corresponds to forme fruste KC definition) were not compared with our study to prevent bias, even if these eyes were defined as subclinical KC in those studies.…”
Section: Discussionmentioning
confidence: 58%
“…Table 8 compares the results obtained with the Pentacam neural network to validate the ESKC model. [35] 68.40 84.60 0.839 Huseynli et al [9] 95.50 73.70 0.904 Hashemi et al [29] 81.10 73.20 0.860 Shetty et al [36] 83.80 86.00 0.887 Ruiseñor Vázquez et al [37] 89.20 82.30 0.930 Ambrósio et al [38] 93.60 94.60 0.975 Steinberg et al [39] 65.80 65.80 0.712 Muftuoglu et al [40] 60.00 90.00 0.834 Castro-Luna et al** 75.00 96.34 0.930 PPI-Avg [3] Cui et al [42] 94.70 89.70 0.957 Huseynli et al [9] 93.30 47.40 0.834 Shetty et al [36] 83.80 74.40 0.883 Ruiseñor Vázquez et al [37] 78.40 82.80 0.860 Muftuoglu et al [40] 77.00 65.00 0.806 Steinberg et al [39] 62.30 64.30 0.669 Uçakhan et al [41] 81.80 77.80 0.842 Castro-Luna et al** 75.00 90.24 0.850 IHD [3] Kovács et al [43] 80.00 75.00 0.880 Bae et al [44] 71.40 85.30 0.748 Huseynli et al [9] 82.30 65.00 0.782 Shetty et al [36] 43.20 67.40 0.627 Uçakhan et al [41] 75.00 60.30 0.703 Castro-Luna et al** 50.00 91.46 0.820 Art-MAX [3] Kovács et al [43] 84.00 54.00 0.740 Shetty et al [36] 86.50 69.80 0.850 Muftuoglu et al [40] 67.00 71.00 0.722 Ruiseñor Vázquez et al [37] 90.50 86.50 0.930 Ambrósio et al [38] 85.10 93.10 0.959 Steinberg et al [39] 30 [44] 71.40 61.80 0.733 Huseynli et al [9] 92.10 52.50 0.844 Hashemi et al [29] 82.30 73.20 0.860 Shetty et al [36] 10.80 95.30 0.609 Uçakhan et al [41] 86.40 61.90 0.768 Castro-Luna et al** 37.50 90.24 0.770 MCT [3] K...…”
Section: The Interpretation With the Effect Of Each Variable Selectedmentioning
confidence: 99%
“…The current version is the BAD III, which utilizes nine tomographic parameters [11]. Studies have shown that among the keratometric, pachymetric, and posterior elevation indices, the D value has the highest area under the receiver operating characteristic curve in differentiating between clinical and subclinical keratoconus (SKC) eyes and control eyes [12,13].…”
Section: Case Presentationmentioning
confidence: 99%